Lyonia lucida, Fetterbush - Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana (EDIS)
FOR 261, a 2-page fact sheet by Michael G. Andreu, Melissa H. Friedman, Mary McKenzie, and Heather V. Quintana, describes this native evergreen shrub found along margins of damp swamp lands and ponds as far north as Virginia, south to Florida, and west to Louisiana — scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, June 2010.